Enriched feeds with iodine and selenium from natural and sustainable sources to modulate farmed gilthead seabream (Sparus aurata) and common carp (Cyprinus carpio) fillets elemental nutritional value. (June 2020) - Barbosa, Vera; Maulvault, Ana Luísa; Anacleto, Patrícia; Santos, Marta; Mai, Mónica; Oliveira, Helena; Delgado, Inês; Coelho, Inês; Barata, Marisa; Araújo‐Luna, Ravi; Ribeiro, Laura; Eljasik, Piotr; et al.
Abstract: Developing tailor-made fortified farmed fish is a promising solution to overcome nutritional deficiencies and increase consumer confidence in these products. This study evaluated the supplementation of three fortified diets with I-rich seaweed and selenised-yeast on essential and toxic elements levels in gilthead seabream ( Sparus aurata ) and common carp ( Cyprinus carpio ). Fortified diets resulted in increased I, Se and Fe in fish muscle. Biofortified seabream and carp revealed lower Cu and Br. The reduction of fishmeal and fish oil in fortified diets resulted in lower Hg and Cd in seabream muscle. Contrarily, fortified diets increased As and Hg in carp fillets. The consumption of 150 g of fortified seabream enabled a significantly higher contribution to the daily recommended intake (DRI) of I (10%) and Se (76%) than non-fortified fish, whereas fortified carp fulfilled 23% of I DRI and 91% of Se DRI. Moreover, the exposure to Pb decreased with the consumption of biofortified seabream (23–82% BMDL01 ) and carp (26–92% BMDL01 ). These results support the strategy of developing eco-innovative biofortified farmed fish using sustainable, natural, safe and high-quality ingredients in feeds, to enable consumers to overcome nutritional deficiencies without significantly increased feed costs. Highlights: Farmed fish biofortification was successfully achieved through I and Se enriched diets from natural and sustainable sources. Biofortified fish fillets yielded a lower exposure to toxic elements, including Hg, Cd and Pb. Iodine fortification was more efficient in common carp, while Se biofortification was more efficient in gilthead seabream. Consumption of biofortified fish provides higher contribution to the DRI of I and Se, without compromising consumer safety.